Inovasi Ecobrick: Solusi Efektif Pengelolaan Sampah Plastik di Desa Sungai Undan - M. Yogi Riyantama Isjoni; Arif Maulana Tambunan; Kamelia Nur Agustin; Siti Nur’Anisah; Intan Tiara Nabila; Alfadhil Trinanda; Lusiana Octavia Simatupang; Habiel Ananda; T. Zuriyati Fazumi; Ikhsan Kurnia Fadillah; Fayza Azzahrah Sianipar (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The cleanliness of the environment plays a crucial role in the welfare of the community. However, the plastic waste problem remains a serious challenge in Sungai Undan Village, Reteh District. This article examines the potential of ecobrick utilization as a solution for reducing plastic waste, focusing on the development of community-based waste management facilities. This program aims to educate the community about the importance of waste management through ecobrick methods and the creation of organic and inorganic waste bins, in order to create a cleaner and healthier environment. The results show that through ecobrick utilization and the provision of separate organic-inorganic waste bins, the community is able to contribute significantly to environmental cleanliness. Sungai Undan Village can thus serve as a model for sustainable waste management.